Sustained Auditory Attentional Load Decreases Audiovisual Integration in Older and Younger Adults - Yanna Ren; Yawei Hou; Jiayu Huang; Fanghong Li; Tao Wang; Yanling Ren; Weiping Yang (Neural Plasticity)
The modulation of attentional load on the perception of auditory and visual information has been widely reported; however, whether attentional load alters audiovisual integration (AVI) has seldom been investigated. Here, to explore the effect of sustained auditory attentional load on AVI and the effects of aging, nineteen older and 20 younger adults performed an AV discrimination task with a rapid serial auditory presentation task competing for attentional resources. The results showed that responses to audiovisual stimuli were significantly faster than those to auditory and visual stimuli (AV>V≥A, all p<0.001), and the younger adults were significantly faster than the older adults under all attentional load conditions (all p<0.001). The analysis of the race model showed that AVI was decreased and delayed with the addition of auditory sustained attention (no_load>load_1>load_2>load_3>load_4) for both older and younger adults. In addition, AVI was lower and more delayed in older adults than in younger adults in all attentional load conditions. These results suggested that auditory sustained attentional load decreased AVI and that AVI was reduced in older adults.